Towards a smart biosafety regulation: the case of Kenya - Kingiri, A.; Ayele, Seife (EDP Sciences, 2009)
It is emerging that benefits of new innovations in agricultural biotechnology may not be realised without appropriate biosafety regulatory mechanisms. The Kenyan regulatory experiences related to regulation of genetically engineered (GE) agricultural activities are explored to provide some basis for defining the challenges involved in biosafety regulation. The various shortcomings in the way the Kenyan biosafety process has been implemented are consistent with the way regulatory systems have been evolving in Africa. The proposed adoption of a “smart regulation” provides the basis for a learning process through which subsequent biotechnology policy initiatives can be improved.